2024
DOI: 10.1021/acs.jafc.3c07535
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Analysis Reveals the Potential Mechanisms for Improving Carotenoid Production in Rhodosporidium toruloides Z11 under Light Stress

Hao Gao,
Yunhan Tang,
Rui Lv
et al.

Abstract: Carotenoids, as a type of tetraterpene compound, have been widely used in food, medical, and health areas owing to their antioxidant, immune enhancement, and disease risk reduction effects. Rhodosporidium toruloides is a promising oleaginous red yeast that can industrially synthesize carotenoids. In this study, the effects of different light exposure times and intervals on carotenoid production by R. toruloides Z11 were first investigated. Results showed that a higher carotenoid content (1.29 mg/g) can be achi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…In this research, authors confirmed that green LEDs (3473 µg/L) and red LEDs (3497 µg/L) increased carotenoid production by 93.5 and 94.9%, respectively. Gao et al [64] reported that R. toruloides Z11 showed higher carotenoid content (1.29 mg/g) when exposed to light for 12 h daily. Production was increased by 1.98 times compared to dark cultivation.…”
Section: Lightmentioning
confidence: 99%
“…In this research, authors confirmed that green LEDs (3473 µg/L) and red LEDs (3497 µg/L) increased carotenoid production by 93.5 and 94.9%, respectively. Gao et al [64] reported that R. toruloides Z11 showed higher carotenoid content (1.29 mg/g) when exposed to light for 12 h daily. Production was increased by 1.98 times compared to dark cultivation.…”
Section: Lightmentioning
confidence: 99%
“…Carotenoids, high-value natural pigments, rich in fruits and vegetables with antioxidant, antiaging, immune-regulating, and other health benefits, are widely used as nutraceuticals in foods and supplements . Naturally occurring carotenoids primarily exist in the all- E -configuration, but during food processing and digestion, they are susceptible to isomerize into common 9- Z - and 13- Z -isomer due to conjugated double-bond structures (Figure ).…”
Section: Introductionmentioning
confidence: 99%